Influence of protein level and supplementary L-methionine and lysine on growth performance and fur quality of blue fox (Alopex lagopus) - Dahlman, Tuula; Valaja, Jarmo; Niemelä, Paavo; Jalava, Taina (Zaklad Narodowy Imienia Ossolinskich, Wydawnictwo Polskiej Akademii Nauk, 2002)
v 2002 ok